2019
DOI: 10.2340/00015555-3207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCR3 and CCR4 Suggests a Poor Prognosis in Mycosis Fungoides and Sézary Syndrome

Abstract: SIGNIFICANCECutaneous T-cell lymphomas are a heterogeneous group of extranodal non-Hodgkin's lymphomas that are characterized by a cutaneous infiltration of malignant monoclonal T lymphocytes. Tumor cells in cutaneous T-cell lymphoma express limited numbers of chemokine receptors on their cell surface. We analyzed the expression patterns of CXCR3, CCR3, CCR4 and CCR10 in skin samples from patients with cutaneous T-cell lymphoma. In addition, we investigated the relationship between chemokine receptor expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In addition to CCR4 ligands, in this study, we investigated CCL19, CXCL10, and CXCL13, which are described as ligands for CCR7, C‐X‐C Motif Chemokine Receptor (CXCR) CXCR3, and CXCR5, respectively. Notably, these chemokine receptors are also expressed in CTCL cells 13‐15 . No differences were identified in the serum levels of CCL19, CXCL10, or CXCL13 among responders and non‐responders to mogamulizumab therapy, suggesting that CTCL cells in MF might not affect the production of these chemokines.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to CCR4 ligands, in this study, we investigated CCL19, CXCL10, and CXCL13, which are described as ligands for CCR7, C‐X‐C Motif Chemokine Receptor (CXCR) CXCR3, and CXCR5, respectively. Notably, these chemokine receptors are also expressed in CTCL cells 13‐15 . No differences were identified in the serum levels of CCL19, CXCL10, or CXCL13 among responders and non‐responders to mogamulizumab therapy, suggesting that CTCL cells in MF might not affect the production of these chemokines.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, these chemokine receptors are also expressed in CTCL cells. [13][14][15] No differences were identified in the serum levels of CCL19, CXCL10, or CXCL13 among responders and non-responders to mogamulizumab therapy, suggesting that CTCL cells in MF might not affect the production of these chemokines.…”
Section: Discussionmentioning
confidence: 96%
“…Since CTCL is a rare disease, and since established criteria for staging and response evaluation for CTCL are limited, few prospective clinical trials for advanced CTCL have been reported, and guidelines for the treatment of CTCL have yet to be established (2, 3). Instead, several preclinical studies have been used to determine the optimal therapy for CTCL (46). Among them, Shono et al reported that mycosis fungoides (MF), the most common subtype of CTCL, shows high expression of CCR4 on the cell surface, correlating with poor prognosis of MF (4).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, several preclinical studies have been used to determine the optimal therapy for CTCL (46). Among them, Shono et al reported that mycosis fungoides (MF), the most common subtype of CTCL, shows high expression of CCR4 on the cell surface, correlating with poor prognosis of MF (4).…”
Section: Introductionmentioning
confidence: 99%
“…T cell lymphoma In MF and SS, CCR4 + cell numbers increase in parallel with disease progression [128], and higher expression of CCR3 and CCR4 by lymphomatous cells in skin samples is associated with poor survival [141]. In MF, sTARC/ CCL17 were significantly higher in tumor stage than in patch or plaque stage [127].…”
Section: Discussionmentioning
confidence: 99%